Introduction to mathematica ® for physicists - Grozin, Andrey (Graduate Texts in Physics,, 2014)
Mathematica is the most widely used system for doing mathematical calculations by computer, including symbolic and numeric calculations and graphics. It is used in physics and other branches of science, in mathematics, education and many other areas. Many important results in physics would never be obtained without a wide use of computer algebra. This book describes ideas of computer algebra and the language of the Mathematica system. It also contains a number of examples, mainly from physics, also from mathematics and chemistry. After reading this book and solving problems in it, the reader will be able to use Mathematica efficiently for solving his/her own problems.